Penerapan Diagetic Sound Pada Film Dokudrama “Bondar Hatabosi” - Giovani Gio Vani; Dwinta Arswendah (ROLLING, 2023)
The artwork "The Role of Sound in the Bondar Hatabosi Docudrama Film" aims to create a docudrama film that provides a reflection on how the importance of natural and environmental sounds in the form of culture in Luat Hatabosi village is especially able to shape the emotions of the audience who hear it. The creation of this film is in the docudrama genre because it tells a story based on a true story from historical re-enactment with elements of dramatization. For this reason, the use of real sound is very appropriate to the genre of this film, namely docudrama. The object of creating this work of art is the sounds of nature and the environment in the form of culture in Luat Hatabosi village so that it can play an important role in the docudrama film "Bondar Hatabosi", such as forming emotions in the audience. The audience's emotions in question, such as positive vibrations, relaxation, calm, and so on, are caused by the nature of natural sounds which are able to stimulate the brain in controlling human emotions. The concept for creating this work focuses on the diegetic sound aspect. Diegetic sound itself is all forms of sound contained in the story world of the film. Diegetic sound in films combines it into two forms, namely onscreen sound and offscreen sound. The sound on the screen is defined as all the sounds produced by the actors in the story and the objects in the frame. Meanwhile, offscreen sound is defined as all sound produced from outside the frame.